2023
DOI: 10.1186/s12888-023-04593-3
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of stress among medical students in Syria and its association with social support: a cross-sectional study

Abstract: Introduction Chronic stress can interrupt personal life and cause fatigue, inability to concentrate, and irritability. This study aims to determine the prevalence of stress and its associated factors among medical students in Syria and whether social support could be a protective factor against stress. Methods A cross-sectional study was conducted in the faculty of medicine of five Syrian universities. The Medical Student Stressor Questionnaire (MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…A similar study from Syria reported that the prevalence of stress among medical students was 87.6%, and academic-related stressors were the most important in terms of perceiving stress [25]. Furthermore, academic-related problems were the most significant factors found to be associated with stress in a Malaysian university [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study from Syria reported that the prevalence of stress among medical students was 87.6%, and academic-related stressors were the most important in terms of perceiving stress [25]. Furthermore, academic-related problems were the most significant factors found to be associated with stress in a Malaysian university [26].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Damascus, students who lived outside Damascus suffered from more stress than those who lived inside Damascus in terms of teaching-, learning-, and social-related stressors. However, living inside Damascus caused students to perceive more moderate stress regarding academic-, and interpersonal-, and intrapersonal-related stressors [25]. Residence outside the university's city causes students to face transportation pressure and take more time to arrive at their college; thus, they become more tired and stressed due to arriving late.…”
Section: Discussionmentioning
confidence: 99%
“…This finding can be explained by social support theory. Family members and friends are the solid psychological and spiritual backing of individuals (a form of social support) (Al Houri et al, 2023 ), and the more social support an individual receive, the more conducive to the shaping of good behaviour (Münzer et al, 2017 ). Our participants were university students, for whom living in shared student accommodation is the most important way of living, followed by living at home, and classmates and family members are the main sources of social support.…”
Section: Discussionmentioning
confidence: 99%
“…Stresor terkait akademik adalah penyebab stres terpenting di kalangan mahasiswa (Al Houri et al, 2023). Faktor yang ditenggarai berhubungan dengan stres akademik yaitu dukungan sosial.…”
Section: Pembahasanunclassified